(untitled) (International Journal of Academic Research in Progressive Education and Development, 2022)
The purpose of the study was to identify the levels of statistical thinking among students of Al-Ghad International College for Applied Medical Sciences in the Kingdom of Saudi Arabia and the effect of gender differences. The study used quantitative data collection methods for one group such as observation checklists and qualitative data collection methods such as interviews and focus group discussion. Performance tasks were designed to classify students according to Langrall and Mooney (2002) statistical thinking evaluation framework. Each task has its own subtasks and objectives spread over four statistical skills in which validity and reliability were verified. The data was yielded from the measurements of 41 students’ statistical thinking levels enrolled in biostatistics course in the first semester of the academic year 2018-2019. The results showed that the level of overall students’ statistical thinking abilities was at the transitional level, followed by the idiosyncratic and quantitative levels respectively, while none of them reached the analytical level. The results also showed that there are no statistically significant differences in students’ thinking levels attributed to gender. The study recommended the necessity of linking statistical activities to the reality of students’ lives and specializations, focusing on the practical aspects rather than the theoretical ones, holding training programs to develop the capabilities of faculty members to classify their students according to their level of statistical thinking, and creating programs to develop statistical thinking among students.